1997
DOI: 10.1177/014860719702100296
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Extra‐Carbohydrate Supplementation in the Late Evening on Energy Expenditure and Substrate Oxidation in Patients With Liver Cirrhosis

Abstract: These preliminary data suggest that extra-carbohydrate supplementation before bedtime can shorten nocturnal fasting with a more economic fuel utilization and effectively diminish fat and protein oxidation in cirrhotic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(68 citation statements)
references
References 22 publications
3
64
0
1
Order By: Relevance
“…Theoretically, LES should shorten nocturnal fasting. In the previous studies with cirrhosis patients, LES has been shown to improve fuel utilization (Chang et al, 1997;Verboeket-van de Venne et al, 1995) and nitrogen economy (Zillikens et al, 1993;Swart et al, 1989). Late evening snack with liquid nutrient (Ensure Liquid) increased RQ and carbohydrate oxidation rates (Miwa et al, 2000).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Theoretically, LES should shorten nocturnal fasting. In the previous studies with cirrhosis patients, LES has been shown to improve fuel utilization (Chang et al, 1997;Verboeket-van de Venne et al, 1995) and nitrogen economy (Zillikens et al, 1993;Swart et al, 1989). Late evening snack with liquid nutrient (Ensure Liquid) increased RQ and carbohydrate oxidation rates (Miwa et al, 2000).…”
Section: Discussionmentioning
confidence: 97%
“…A late evening snack (LES) was recommended to minimize early starvation for overnight fasting in cirrhotic patients. It has been reported that supplementation of extra carbohydrate (Chang et al, 1997), oral branched chain amino acids (BCAA) (Yamauchi et al, 2001;Okamoto et al, 2003;Tsuchiya et al, 2005) and a-glucosidase inhibitor given with LES , all improved energy metabolism in cirrhotic patients. Therefore, LES supplementation to prevent early-onset starvation, and energy deficiency may be advisable in such patients to maintain nourishment.…”
Section: Introductionmentioning
confidence: 99%
“…Nutritional recommendations for cirrhotic patients with HE should follow ISHEN practice consensus recently published by Amodio et al 15 These recommendations, including specific pattern of dietary intake, 133,134 which should also be based on individual nutritional assessment, are summarized in Table 2.…”
Section: Nutritional Recommendations For He In Cirrhosismentioning
confidence: 99%
“…[12][13][14][15] However, there is no consensus in the data on energy expenditure, and thus energy requirements, in this patient population. [16][17][18][19][20][21][22] Plauth et al 23 recommended that energy requirements should be determined in patients with cirrhosis by measurement of their resting energy expenditure (REE) using indirect calorimetry. They suggest, but do not advocate, that if the facilities for measurement are not available, then energy expenditure could be estimated by use of the Harris-Benedict prediction formulae.…”
mentioning
confidence: 99%